Vocabulary Improvement Using Bilingual Magazines In SMA Negeri 4 Palopo Students - Berkah Bahari; Husnani Aliah; Nasriand (Universitas Serambi Mekkah, 2023)
This study aims to explain the improvement of students' vocabulary about nouns (abstract nouns and concrete nouns), verbs (regular verbs and irregular verbs) adjectives (descriptive adjectives). This research method is an experimental method consisting of four meetings thus this research was conducted at SMA NEGERI 4 PALOPO and the subjects in this study were students of class XI IPA 1, from this study the students' scores were mastery of vocabulary through bilingual magazines before using this media in teaching and learning vocabulary, the average score of students was 49 (not good) after using bilingual magazines as a medium for the teaching and learning process increased to 89 (very good). Based on the test results, the researchers found that the correlation P of the post-test at the end of the experiment was greater than (0.01<.05) the test value at the end of the experiment. This indicates that the alternative hypothesis (H1) is accepted, and the hypothesis (H0) is rejected. It has been established that the use of Bilinguals enhances the effectiveness of the game.